The Influence of Taking Note on Listening Comprehension in The Pre-Intermediate EFL Students - Dita Fitri Agasty Sofiana; Herri Akhmad Bukhori (Pascasarjana UM, 2021)
Abstract: The study defined aboutaffecting taking note toward Pre-Intermediate EFL student’s listening comprehension. The study accomplishedquantitative method especially quasi experimental research. Test and questionnaire were parts of intruments in this study. Finding of this study showed that there isdisparity from the result of students’ listening comprehension between experimental and control group, there is affecting of taking note toward students’ listening comprehension and there are difficulties of implementation of taking note toward listening comprehension.Keywords: taking note, listening comprehension, Pre-Intermediate EFL students Abstrak: Penelitian ini menjelaskan tentang pengaruh strategi taking note terhadap pemahaman menyimak mahasiswa EFL Pre-Intermediate. Penelitian ini menggunakan metode kuantitatif khususnya penelitian quasi eksperimen.Tes dan angketadalah bagian dari instrumen dalam penelitian ini. Penemuan dalam penelitian ini menunjukkan bahwa terdapat perbedaan dari hasil pemahaman menyimak siswa antara kelompok eksperimental dan kelompok kontrol, terdapat pengaruh dari taking note terhadap pemahaman menyimak mahasiswa dan terdapat kesulitan – kesulitan dalam penerapan taking note terhadap pemahaman menyimak mahasiswa.Kata kunci: mencatat, pemahaman mendengarkan, siswa EFL Pra-Menengah